Effect of support and reduction temperature in the hydrogenation of CO2 over the Cu–Pd bimetallic catalyst with high Cu/Pd ratio. (30th July 2022) - Xu, Yamei; Ding, Ziluo; Qiu, Rui; Hou, Ruijun
Abstract: Metal-support interaction and catalyst pretreatment are important for industrial catalysis. This work investigated the effect of supports (SiO2, CeO2, TiO2 and ZrO2 ) for Cu–Pd catalyst with high Cu/Pd ratio (Cu/Pd = 33.5) regarding catalyst cost, and the reduction temperatures of 350 °C and 550 °C were compared. The activity based on catalyst weight follows the order of Si > Ce > Zr > Ti when reduced at 350 °C. The reduction temperature leads to the surface reconstruction over the SiO2, CeO2 and TiO2 catalysts, while results in phase transition over Cu–Pd/ZrO2 . The effect of reduction temperature on catalytic performance is prominent for the SiO2 and ZrO2 supported catalysts but not for the CeO2 and TiO2 ones. Among the investigated catalysts, Zr-350 exhibits the highest methanol yield. This work reveals the importance of the supports and pretreatment conditions on the physical-chemical properties and the catalytic performance of the Cu–Pd bimetallic catalysts. Highlights: Phase separation exists over Si-350, Si-550, Ti-350, Zr-350 and Zr-550. The TOF over Si-350 is higher than the other three catalysts (280 °C). Reduction temperature leads to the phase transition over ZrO2 catalysts. Surface structure reconstruction caused by reduction temperature exist over SiO2, CeO2 and TiO2 catalysts. Effect of reduction temperature is prominent over the SiO2, CeO2 and ZrO2 supported catalysts.